Host-Defense Peptides Caerin 1.1 and 1.9 Stimulate TNF-Alpha-Dependent Apoptotic Signals in Human Cervical Cancer HeLa Cells - Ni, Guoying; Chen, Shu; Chen, Mo; Wu, Jialing; Yang, Binbin; Yuan, Jianwei; Walton, Shelley F.; Li, Hejie; Wei, Ming Q.; Wang, Yuejian; Chen, Guoqiang; Liu, Xiaosong; et al. (Frontiers in Cell and Developmental Biology, 2020)
Host defense caerin 1.1 and 1.9 peptides, isolated from the glandular secretion of Australian tree frogs, the genus Litoria, have been previously shown to have multiple biological activities, including the inhibition of human papillomavirus (HPV) 16 early protein E7 transformed murine as well as human cancerous cell proliferation both in vitro and in vivo. However, the mechanism underlying their anti-proliferative activities against HPV18+ cervical cancer HeLa cells remains unknown. This study comparatively investigated the anti-proliferation on HeLa cells by caerin 1.1, 1.9 and their mixture, followed by confocal microscopy examination to assess the cellular intake of the peptides. Tandem mass tag labelling proteomics was employed to reveal the proteins that were significantly regulated by the peptide treatment in cells and cell growth environment, to elucidate the signalling pathways that were modulated. Western blot was performed to confirm the modulation of the pathways. Both caerin 1.1 and 1.9 highly inhibited HeLa cell proliferation with a significant additive effect compared to untreated and control peptide. They entered the cells with different magnitudes. Intensive protein-protein interaction was detected among significantly upregulated proteins. Translation, folding and localisation of proteins and RNA processing, apoptosis process was significantly enriched post the treatments. The apoptotic signalling was suggested as a result of tumour necrosis factor-α (TNF-α) pathway activation, indicated by the dose-dependent elevated levels of caspase 3 and caspase 9. The epidermal growth factor receptor and androgen receptor pathways appeared inhibited by the peptides. Moreover, the activation of T-cell receptor derived from the quantitation results further implies the likelihood of recruiting more T cells to the cell growth environment post the treatment and more sensitive to T cell mediated killing of HeLa cells. Our results indicate that caerin 1.1 and 1.9 mediate apoptotic signals of HeLa cells and may subsequently enhances adaptive T cell immune responses.